The Civil War political tradition : ten portraits of those who formed it - Escott, Paul D., 1947- (Nation divided., 2023)
"Offers biographical sketches of ten prominent Americans who confronted the central issues of the Civil War era-slavery, racism, and equality-evaluating their careers and shedding light on leadership, core American values, and problems plaguing US democracy. Those profiled include John C. Calhoun, Henry Clay, Jefferson Davis, Stephen A. Douglas, Frederick Douglass, Horace Greeley, Abraham Lincoln, Elizabeth Cady Stanton, Harriet Beecher Stowe, and Albion Tourgée"--